2013
DOI: 10.5012/bkcs.2013.34.3.783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carbon Dioxide Absorption in Aqueous MEA, DEA, TEA, and AMP Solutions

Abstract: The separation and capture process of carbon dioxide from power plants is garnering interest as a method to reduce greenhouse gas emissions. In this study, aqueous alkanolamine solutions were studied as absorbents for CO 2 capture. The solubility of CO 2 in aqueous alkanolamine solutions was investigated with a continuous stirred reactor at 313, 333 and 353 K. Also, the heat of absorption (−ΔH abs ) between the absorbent and CO 2 molecules was measured with a differential reaction calorimeter (DRC) at 298 K. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 14 publications
9
74
1
Order By: Relevance
“…For secondary amines the binding energy is assumed to be 70 kJ/mol CO 2 . It is in the same range as reported by Kim et al [65].…”
Section: Extractions From Wet Algae Slurrysupporting
confidence: 87%
“…For secondary amines the binding energy is assumed to be 70 kJ/mol CO 2 . It is in the same range as reported by Kim et al [65].…”
Section: Extractions From Wet Algae Slurrysupporting
confidence: 87%
“…The heat of absorption reported for AMP in EG and in aqueous solutions shows a slower decrease, which is probably due to the formation of bicarbonate in aqueous AMP solutions and the contribution from the reaction of EG with the zwitterion (RNH + 2 COO − ), at higher loadings. Kim et al (2013) reported a heat of absorption for an aqueous solution of 30 wt% AMP of −63.95 kJ/mol CO 2 at a CO 2 loading of 0.862 mol CO 2 /mol AMP at 25 • C. This is slightly higher than the values reported by Mehdizadeh et al (2013), but lower than those reported by Arcis et al (2008) for the same AMP concentration. Fig.…”
Section: Tablecontrasting
confidence: 68%
“…Surprisingly, the atmospheric level of CO2 has reached a significantly symbolic milestone, 400 parts per million (Scripps Institution of Oceanography, 2017), and moreover, a further continuous increase is expected for the foreseeable future in the absence of proper actions (Kim et al, 2013). In the context of global awareness of this issue, in 2015 COP21, also known as the 2015 Paris Climate Conference, proposed an agreement to keep the global average temperature rise below 2°C above preindustrial levels by limiting total carbon emissions in the atmosphere (COP21, 2015).…”
mentioning
confidence: 99%